Efficacy of language intervention in the early years - Fricke, S; Bowyer-Crane, C; Haley, A; Hulme, C; Snowling, M (2013)
Background: Oral language skills in the preschool and early school years are critical to educational success and provide the foundations for the later development of reading comprehension. Methods: In a randomized controlled trial, 180 children from 15 UK nursery schools (n = 12 from each setting; M age = 4;0) were randomly allocated to receive a 30-week oral language intervention or to a waiting control group. Children in the intervention group received 30 weeks of oral language intervention, beginning in nursery (preschool), in three group sessions per week, continuing with daily sessions on transition to Reception class (pre-Year 1). The intervention was delivered by nursery staff and teaching assistants trained and supported by the research team. Following screening, children were assessed preintervention, following completion of the intervention and after a 6-month delay. Results: Children in the intervention group showed significantly better performance on measures of oral language and spoken narrative skills than children in the waiting control group immediately after the 30 week intervention and after a 6 month delay. Gains in word-level literacy skills were weaker, though clear improvements were observed on measures of phonological awareness. Importantly, improvements in oral language skills generalized to a standardized measure of reading comprehension at maintenance test. Conclusions: Early intervention for children with oral language difficulties is effective and can successfully support the skills, which underpin reading comprehension. © 2012 The Authors. Journal of Child Psychology and Psychiatry © 2012 Association for Child and Adolescent Mental Health.